Using design-based implementation research approach to create computational thinking assessment tools for youth programs in public libraries - Koren, Nitzan; Weintrop, David; Subramaniam, Mega (Library & information science research, 2023)
Methodological innovations across social sciences are opening new avenues for conducting research designed to address real-world challenges. The benefits of utilizing the Design-Based Implementation Research (DBIR) approach in public libraries to resolve a persistent problem of practice, a lack of assessment tools to evaluate youth Computational Thinking (CT) programs, is demonstrated. Findings from a three-year, three-phased study utilizing the DBIR approach to design and implement a suite of assessment tools to assess CT programming in public libraries are presented. Guided by the four principles of the DBIR approach, this research produced new knowledge, including identifying CT program outcomes, challenges, and recommendations for designing and implementing assessment tools to measure the impact of public libraries' CT programming. Findings underscore the DBIR approach as a strategy for engaging with practitioners and helping shift their perspectives by resolving practice problems and facilitating the design of sustainable solutions. •The Design-Based Implementation Research approach highlighted library staff needs by seeking sustainable solutions.•Participating in Computational Thinking (CT) assessment design led staff to focus on learning outcomes.•Involving multiple stakeholders yielded a broad understanding of CT outcomes, challenges, and programmatic needs.•Iterating with library staff allowed staff to shape the assessment tools to fit their needs.